Attrition in rape and sexual assault cases - Gregory, Jeanne (The British journal of criminology, 1996)
This article presents the key findings of a research project investigating changing police policies and practices at two London police stations in relation to rape and sexual assault cases. Despite a shift to the more sensitive treatment of women reporting sexual attacks, the attrition rate remains high. The police practice of no-criming' a high proportion of cases is compounded by the negative role of the Crown Prosecution Service and the extreme difficulty of securing a conviction when cases do come to court. The paper concludes by emphasizing the need for a radical overhaul of the judicial process